Can Environmental Risk Management Improve the Adaptability of Farmer Households’ Livelihood Strategies? ——Evidence From Hubei Province, China - Zhang, Chongmei; Luo, Xin; Song, Jiahao; Fu, Zhuoying; Huang, Zeng; Wang, Wei (Frontiers in Environmental Science, 2022)
With the rising temperature, uneven precipitation and frequent occurrence of extreme weather caused by global climate change, agricultural production is facing more severe challenges. Based on the sustainable livelihoods framework, this paper measures the index of farmer households' livelihood strategy adaptability and analyzes the benefits of farmer households' environmental risk management on livelihood strategy adaptability by using microscopic research data of 970 farmer households' livelihoods in Hubei Province, China, in 2020. This paper found that the farmer households' environmental risk management variables have a significant impact on the adaptability of farmer households' livelihood strategies, with the stronger the farmer households' environmental risk management capacity, the more adaptable its livelihood strategy. The impact of farmer households' environmental risk management variables on livelihood strategies varies for farmer households with different income levels. Therefore, this paper proposes that we should improve farmers' perception of climate change, promote the diffusion of adaptive technologies, improve agricultural insurance policies, give full play to the collective role of village collectives, companies and cooperatives, and promote the transformation and upgrading of livelihood approaches to further improve the adaptability of livelihood strategies.